Study of automation of insert potting process - Kwek, Gilbert Chang Run (2018)
Honeycomb panels have been used widely in aerospace industries due to its lightweight and strong material properties. This report present results from the studies of automation of insert potting process. Studies were carried out to understand the concept of Honeycomb panel and Insert Potting Process, potting compound and its purpose, importance of repeatability and dispensing system as well as Pick & Place system. Tests were performed to check on the material properties and the curing time of the honeycomb with Stycast 1090/Catalyst 11 compound. Along the way, idea generations and design conceptualisation were done to create prototype for testing. Experiments were done on the final bracket prototype that can substitute manual processes. Lastly, this report provides recommendations that will help to improve on the efficiency of the Insert potting process by automation.